Melancolia e transcendência na obra poética de Camilo Pessanha - Chagas, Ibiraci de Alencar (2011)
It is argued in this paper, the concepts of melancholy and transcendence are present in the poetry of Camilo Pessanha. Diving into the symbolic universe of the Portuguese poet, we map the occurrence melancholy of loss, in which one loses an object never before possessed, and which may develop in the form of an experience transcendental, which breaks the conventional boundaries of perception and opens up new dimensions of consciousness.